MENANAMKAN NILAI-NILAI KARAKTER BERPOLA PEMBIASAAN PERILAKU DI TAMAN KANAK- KANAK ROSIHAN ANWAR - Ashar - Ashar; Sadaruddin - Sadaruddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2019)
The purpose of this study is to inculcate character values based on patterns of habitualizing behavior in early childhood, so that they can contribute actively behaving in positive activities that are fun in raising the character values. This research method is to describe the condition of